Democracy's fourth wave? digital media and the Arab Spring - Howard, Philip N.; Hussain, Muzammil M. (Oxford studies in digital politics., 2013)
In 2011, the international community watched as citizens mobilized through the Internet and digital media to topple three of the world's most entrenched dictators: Ben Ali in Tunisia Mubarak in Egypt, and Qaddafi in Libya. This book examines not only the unexpected evolution of events during the Arab Spring but the longer history of desperate - and creative - digital activism through the Arab world.